2018
DOI: 10.1016/j.ijmm.2017.11.005
|View full text |Cite
|
Sign up to set email alerts
|

The use of stool specimens reveals Helicobacter pylori strain diversity in a cohort of adolescents and their family members in a developed country

Abstract: HighlightsConcentration of H. pylori in feces before DNA isolation enhances DNA amplification.Analysis of DNA in feces allows for H. pylori transmission studies in communities.Multiple strains are commonly found in infected individuals.Family members can harbor strains not found in other family members.Infection with multiple strains has implications for antibiotic sensitivity testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 50 publications
0
11
0
2
Order By: Relevance
“…A relatively small cross-sectional study was recently reported in Turkey confirming the previous evidence of more frequent infection in larger families with other infected members. 28 Similar H pylori strains were most commonly found in both mothers and children and in siblings; 40% of the individuals had multiple strains, and several individuals harbored strains not found in other family members. 28 Similar H pylori strains were most commonly found in both mothers and children and in siblings; 40% of the individuals had multiple strains, and several individuals harbored strains not found in other family members.…”
Section: Family Transmission and Interaction With Other Microbiotamentioning
confidence: 92%
See 1 more Smart Citation
“…A relatively small cross-sectional study was recently reported in Turkey confirming the previous evidence of more frequent infection in larger families with other infected members. 28 Similar H pylori strains were most commonly found in both mothers and children and in siblings; 40% of the individuals had multiple strains, and several individuals harbored strains not found in other family members. 28 Similar H pylori strains were most commonly found in both mothers and children and in siblings; 40% of the individuals had multiple strains, and several individuals harbored strains not found in other family members.…”
Section: Family Transmission and Interaction With Other Microbiotamentioning
confidence: 92%
“…27 A H pylori stool DNA-based study on 50 individuals in 13 families was reported from Ireland. 28 Similar H pylori strains were most commonly found in both mothers and children and in siblings; 40% of the individuals had multiple strains, and several individuals harbored strains not found in other family members. The same study group concluded that spontaneous H pylori clearance is uncommon in adolescents or adulthood in developed countries 29 ; however, it should be mentioned that the prevalence of the infection was low in this study population.…”
Section: Family Transmission and Interaction With Other Microbiotamentioning
confidence: 92%
“…Another study from Ireland analyzed fecal samples of all family members by PCR for H. pylori typing (n = 82) if a child and at least one family member were H. pylori positive by UBT. Although in the majority of cases, children had a similar strain to that of their mothers and siblings, multiple strain infection was demonstrated in a high proportion (37.7%) of individuals, thus suggesting that even in industrialized countries, H. pylori could be acquired outside the family …”
Section: Epidemiologymentioning
confidence: 99%
“…Although in the majority of cases, children had a similar strain to that of their mothers and siblings, multiple strain infection was demonstrated in a high proportion (37.7%) of individuals, thus suggesting that even in industrialized countries, H. pylori could be acquired outside the family. 3…”
Section: Studied H Pylori Incidence Inmentioning
confidence: 99%
“…pylori ha sido cultivado a partir de heces de individuos infectados (Thomas et al, 1992;Kelly et al, 1994;Falsafi et al, 2007), existiendo cada vez más evidencias que sugieren una ruta de transmisión fecal-oral para H. pylori (Mladenova et al, 2006). Sin embargo, esta ruta sigue siendo cuestionada, ya que la concentración de H. pylori en las heces es considerada baja, particularmente cuando se compara con la de otros patógenos fecales de importancia en la salud pública (Dolan et al, 2018). Además, el cultivo de H. pylori a partir de heces se ha conseguido en muy pocas ocasiones, aunque la presencia de sus antígenos y su DNA en heces de individuos infectados es un hecho común (Ford y Axon, 2010).…”
Section: Modo De Transmisiónunclassified